2018
DOI: 10.3390/rs10020245
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Limitation in Damage Detection for Individual Buildings Using InSAR Coherence—A Case Study in 2016 Kumamoto Earthquakes

Abstract: Abstract:In this paper, evaluation results are presented for multi-temporal interferometric coherence analysis using a Synthetic Aperture Radar (SAR) for damage assessment in an urban area. The latest space-borne SARs potentially have a high enough spatial resolution to assess individual buildings. However, interferometric coherence analysis has not been evaluated for its limitation in sensitivity and size of damaged buildings. In particular, the correlation between the coherence analysis and the damage level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The threshold is generally defined manually to reduce the effect of temporal and spatial decorrelations. In [39], the authors found that the buildings which are larger than 200m 2 can be evaluated by setting the threshold 0.3. When the buildings exceed the threshold, they were moderately or severely damaged when they are classified by EMS-98 scheme [40].…”
Section: Interferometric Coherence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The threshold is generally defined manually to reduce the effect of temporal and spatial decorrelations. In [39], the authors found that the buildings which are larger than 200m 2 can be evaluated by setting the threshold 0.3. When the buildings exceed the threshold, they were moderately or severely damaged when they are classified by EMS-98 scheme [40].…”
Section: Interferometric Coherence Analysismentioning
confidence: 99%
“…Region U and V, moderately damaged and collapsed buildings, can be detected by interferometric coherence analysis too. Its sensitivity is discussed precisely in [39].…”
Section: Scattering Mechanisms Of Harbor Facilitiesmentioning
confidence: 99%
“…We conducted Interferometry Synthetic Aperture Radar (InSAR) observations together with GPS/GIS data analysis and geophysical modelling to assess the vulnerability of Ulsan to surface deformation, and focused on the relationship between recent (2015-2018) and future potential seismic activities and the plausible risks of industrial infrastructure. InSAR techniques have been employed to investigate the effects of seismic activity and surface deformation in a large number of studies; it is a well-demonstrated method for determining potential hazards, particularly earthquakes [22][23][24], and for evaluating the associated damage [25][26][27]. However, our aim was to investigate the effects of relatively minor earthquakes and to monitor the potential damage from accumulated subtle strain over highly sensitive infrastructure facilities.…”
Section: Of 23mentioning
confidence: 99%
“…Furthermore, these two parameters are sometimes combined to conduct building damage detection [20,21]. Due to the development of high-spatialresolution (HR) and very-high-spatial-resolution (VHR) SAR images, an increasing number of change detection methods have been proposed to detect building damage at the individual building level [22][23][24][25][26]. In addition, deep learning-based methods for building change detection have been proposed using VHR SAR images [25,27].…”
Section: Introductionmentioning
confidence: 99%